Vegetable-origin foam employed in dye extraction in tanning and leather processing facilities - Cangemi, José M.; Santos, Antonia M. dos [UNESP]; C. Neto, Salvador; Oshita, Daniele (Associação Brasileira de Polímeros, 2009)
This study addressed the use of conventional and vegetable origin polyurethane foams to extract C. I. Acid Orange 61 dye. The quantitative determination of the residual dye was carried out with an UV/Vis absorption spectrophotometer. The extraction of the dye was found to depend on various factors such as pH of the solution, foam cell structure, contact time and dye and foam interactions. After 45 days, better results were obtained for conventional foam when compared to vegetable foam. Despite presenting a lower percentage of extraction, vegetable foam is advantageous as it is considered a polymer with biodegradable characteristics.
Keywords: Extraction; polyurethane foam; dye